Effect of inhaled corticosteroids on lung function in chronic beryllium disease. (May 2018) - Mroz, Margaret M.; Ferguson, John H.; Faino, Anna V.; Mayer, Annyce; Strand, Matthew; Maier, Lisa A.
Abstract: Background: The clinical effects of inhaled corticosteroids (ICS) on chronic beryllium disease (CBD) are unknown. Although frequently used for symptoms or disease not requiring systemic therapy, the clinical course of patients on ICS has not been evaluated. Methods: In a retrospective cohort study, forty-eight subjects with CBD, diagnosed by granulomas on lung biopsy and treated with inhaled corticosteroids, were matched to sixty-eight subjects with CBD who were not treated. Pulmonary function testing, exercise tolerance, blood BeLPT, BAL cell count, and symptoms were evaluated. Results: Treated patients showed no significant change over time in pulmonary function, when compared to controls, by forced vital capacity (FVC, p = 0.28) or diffusion capacity (DLCO, p = 0.45) or in exercise tolerance testing. However, symptoms of cough significantly improved in 58% (compared to 17% in controls) and dyspnea improved in 26% after ICS treatment (compared to 0 in controls). Symptoms of cough were improved in patients with a lower baseline FEV1 and FEV1/FVC ratio. Subgroup analysis showed significant lung function response in cases with lower baseline FEV1/FVC and higher residual volume (RV). Conclusion: Although FVC and DLCO did not improve in the ICS treated group, we saw no difference in decline compared to matched controls. Symptoms of dyspnea and cough improved with ICS especially in those with obstruction and air trapping suggesting that these should be considered an indication of ICS use in CBD patients. Highlights: Inhaled corticosteroids (ICS) to treat chronic beryllium disease (CBD) was evaluated. ICS maintained pulmonary function decline suggesting a stabilization effect. Treated cases with lung function improvement had evidence of baseline obstruction. Cough significantly improved, especially in patients with lower FEV1 and FEV1/FVC. ICS should be considered in CBD patients with asthma-like presentation and cough.